Applied Gamification to Enhance Customer Loyalty for Fintech Industry - Qureshi, M.A.; Ghulamani, S.; Abdallah, S.S.; Thartori, Voltisa; Khowaja, K.; Mahdi, G.; Shah, A. (2023)
In this study, a mobile application prototype for fintech industry is proposed which aims to addresses users' problems and engage them based on incentivized mechanism through applied gamification used for the users. Users will perform transactions and in return get some points as rewards, which they can use for cashback rewards or send these points to someone they want. For this research, Figma is used as a tool for designing wireframes and prototypes which later included in UseBerry to perform usability tests from users to collect their responses. Around 50 participants have been invited to collect their responses based on using the prototype and answering a few questions based on that. Results have shown an enormously positive response from users who really want to get incentives through their daily transactions and can get whatever benefits they are provided. However, this research is limited to a few features and more features and testing can be done based on the current response from the users which will directly impact user's daily life and improve conversions for the banking and fintech industry.